The Relevance of the Muhammadiyah Concept of Keluarga Sakinah in Reducing Divorce Trends in Indonesia: A Socio-Religious Analysis Based on Community Data - Hector Javier Cortes Tornel; Muhammad Hayat (Prodi Pengembangan Masyarakat Islam Fakultas Dakwah dan Ilmu Komunikasi UIN Mataram, 2025)
The increasing divorce rate in Indonesia over the past decade indicates growing vulnerabilities in family resilience shaped by changes in social, economic, and cultural structures. This article aims to analyze the relevance of the Muhammadiyah concept of Keluarga Sakinah in responding to contemporary divorce trends through a socio-religious approach based on community data. This study employs a non-field research design relying on secondary data analysis, including official Muhammadiyah documents, reports on Muhammadiyah community programs, and divorce statistics issued by the Central Bureau of Statistics (BPS) and the Supreme Court of Indonesia. Therefore, this study concludes that the relevance of the Muhammadiyah concept of Keluarga Sakinah is contextual in nature and requires synergy among religious organizations, the state, and civil society to strengthen family resilience in Indonesia